Finessing incivility: The professional socialisation experiences of student nurses' first clinical placement, a grounded theory. (December 2015) - Thomas, Juliet; Jinks, Annette; Jack, Barbara
Summary: Background: Clinical practice is where student nurses are socialised into a professional role and acquire the distinct behaviour, attitudes and values of the nursing profession. Getting it right at the outset can maximise the development of a professional identity and the transmission of robust value systems. Objectives: To explore the impact of the first clinical placement on the professional socialisation of adult undergraduate student nurses in the United Kingdom. Design: Data of a longitudinal qualitative nature were collected and analysed using grounded theory. Settings: First year student nurses in hospital ward placements comprising a rural District General Hospital and a large inner city Hospital kept daily unstructured diaries for six weeks. Participants: A total of 26 undergraduate adult student nurses were purposefully sampled between 2008 and 2010 before undertaking their initial clinical placement. Methods: Data collection and analysis used grounded theory and the key question asked of the diarists 'tell me what it is like to be a first year nurse on a first placement' was theoretically adjusted during constant comparison and as the theory emerged. Ethical approval and consent was obtained. Results: The theory of finessing incivility comprises a conceptual framework depicting how student nurses deal with professional incivility during their initial clinical placement and sustain a student identity. Being disillusioned with their role as worker rather than learner yields a sense of 'status dislocation'. Despite needing professional benevolence, they remain altruistic and seek recompense from significant others to negotiate for learning opportunities and relocate their student status. Conclusions: Despite the stressful transition into clinical practice rather than 'fit in', the student nurses want to belong as learners. His or her own resilience to learn nursing and be a professional student maintains their resolve, their altruism and strengthens their existing values to be benevolent towards an indifferent profession. This behaviour ultimately mirrors the social nature of the practice community. Highlights: The initial transition into practice is challenging for student nurses. In the face of adversity student nurses display versatility and resilience. Adopting interactionist traits enables students to adapt to clinical realities.